POTENTIAL VALUES OF BACTERIAL CELLULOSE FOR INDUSTRIAL APPLICATIONS - Endang Sukara; Ruth Meliawati (Center for Pulp and Paper, 2014)
Cellulose is the main biopolymer on earth and internationally plays an important role in global economic arena. Along with the current and the future advancement of science and technology, cellulose particularly pure cellulose, has an ample of opportunity to be used as raw materials in modern food, health industry and many other industrial sectors including for the production of advance materials. Currently, the main source of cellulose is that of plant origin which naturally interconnected with lignin to forms materials called lignocellulose. Separation of cellulose from lignocellulose is a complicated process. Meanwhile, cellulose which is synthesized by diverse microbial species, especially bacteria, has many advantages. The purity of bacterial cellulose is very high, better crystalline property, high water absorbency, simple polymerization, stronger, and high bio-compatibility. In this review, recent application of bacterial cellulose in the development of food, health industries as well as advance materials will be discussed.Keywords: bacterial cellulose, nano-crystal, medical device, nanocomposite, biocompatible ABSTRAKSelulosa adalah polimer utama di permukaan bumi dan secara internasional menempati kedudukan penting dalam perkembangan ekonomi dunia. Seiring dengan kemajuan ilmu pengetahuan saat ini dan di masa yang akan datang, selulosa, khususnya selulosa murni, memiliki peluang yang sangat luar biasa sebagai bahan baku pada industri makanan modern, industri kesehatan, dan sektor industri lainnya termasuk industri material maju. Saat ini, sumber selulosa utama adalah tanaman. Selulosa yang berasal dari tanaman selalu berikatan dengan lignin dalam bentuk ligonoselulosa yang memiliki kerumitan untuk memisahkannya. Sementara itu, selulosa yang disintesis oleh berbagai jenis mikroba, khususnya bakteri, memiliki keuntungan yang besar karena tingkat kemurniannya yang tinggi, sifat kristal yang lebih baik, mampu menyerap air, polimerisasi yang sederhana, lebih kuat, dan memiliki daya adaptasi biologis yang tinggi. Dalam tinjauan ini, perkembangan terkini dalam proses pengolahan selulosa yang berasal dari bakteri untuk kepentingan pengembangan industri makanan, kesehatan, dan material maju akan didiskusikan.Kata kunci: bakteri,selulosa, kristal-nano, alat kesehatan,komposit-nano, bio-kompatibel